MODELING OF MUSHROOMS (Agaricus bisporus) OSMOTIC DEHYDRATION PROCESS IN SUGAR BEET MOLASSES - Šuput, Danijela; Filipović, Vladimir; Lončar, Biljana; Nićetin, Milica; Knežević, Violeta; Lazarević, Jasmina; Plavšić, Dragana (Food and Feed Research, 2020)
Mushrooms (Agaricus bisphorus) were osmotically dehydrated in sugar beet molasses solutions at concentrations of 60%, 70% and 80%, at operating temperatures of 25 °C, 35 °C and 45 °C during 0.5h, 1h, 1.5h, 2h, 3h, and 5 hours. Moisture content, water activity (aw), microbial profile (total plate counts, Enterobacteriaceae, total yeasts and moulds count) and mineral matter content (content of potassium, magnesium, iron and calcium) were determined to the obtained osmodehydrated mushroom samples. Response Surface Methodology and Analysis of variance were selected to estimate the main effects of the process variables on osmodehydration process and microbiological, mineral matter and chemical responses. Increase of applied osmotic process parameters values has led to the significant increase of mineral matter content and decrease of aw values, microbiological load and relative protein content, indicating a possibility for prolonged shelf life and further processing. Enriched osmodehydrated mushrooms regarding nutritive profile could be considered for new functional (semi)products.
Keywords: mineral composition; water loss; solid gain; microbiological load; chemical composition